MORAL LESSONS AND VALUES IN UZBEK AND KOREAN FAIRY TALES: AN INSIGHT INTO CULTURAL BELIEFS - Turgunpulatovna, Nargiza Dosbaeva (Journal of Higher Education and Academic Advancement, 2024)
In recent years, Uzbek folklore has become increasingly interested in comparing it with the folklore of other peoples and nationalities. Comparing the features of a number of genres created at the stage of the nation’s literary development - fairy tales, epics, ritual folklore, this article is of great importance in establishing literary cooperation in the era of the Third Renaissance.The common features of Uzbek and Korean folklore genres are the presence of folk heroes and legends, who express courage and resourcefulness, and often go on epic journeys or quests. These heroes are revered in their cultures for their extraordinary qualities and deeds as symbols of strength and virtue